Development of Augmented Reality (AR) Learning Media with the Project-Based Learning Model to Improve Motivation and Learning Outcomes in Projection Drawing - Romi Hartono; I Wayan Sukra Warpala; Kadek Suartama (Universitas Negeri Padang, 2026)
The low level of students’ spatial understanding and the limited availability of dynamic visual media capable of facilitating three-dimensional object representation in projection drawing learning constitute a strategic educational problem. Students often experience difficulties in visualizing spatial relationships, which affects both their motivation and learning outcomes. To address this issue, this study developed augmented reality (AR) learning media using the 4D development model, consisting of Define, Design, Develop, and Disseminate stages. The purpose of this research was to improve students’ learning motivation and learning outcomes in projection drawing instruction. This research was conducted in the Visual Arts Education Study Program at Universitas Pendidikan Ganesha, involving 22 students as research subjects. Data were collected through interviews, observations, questionnaires, tests, and documentation. The research instruments included expert validation sheets, motivation questionnaires, and learning outcome tests. All instruments were validated by content experts, media experts, and instructional design experts. Data analysis techniques comprised descriptive analysis, normality testing, Wilcoxon tests, paired-sample t-tests, and N-gain analysis to determine the effectiveness of the developed media. The results showed that the AR learning media was highly feasible, with a validation score of 91% from content experts and 88% from media experts. Individual, small-group, and field trials indicated positive student responses, with acceptance rates between 81% and 91%. The mean pretest score increased from 41.00 to 72.41 in the posttest, with an N-gain value of 0.52 (moderate category). Students’ learning motivation also increased significantly (p = 0.000). Therefore, the developed AR media is feasible and effective for projection drawing learning.